On Some Types Of N-functions - Al-Janabi, Dr. Sattar Hameed Hamzah (Al-Qadisiyah Journal of Pure Science, 2017)
In this work ,we introduce the definitions of some types of N-functions namely N-irresolute, strongly N-closed and N-perfect, and investigate the properties of composition, restrictions and product of each type. Also, we give the relation among them.